RNA sequencing role and application in clinical diagnostic - Fatemeh Peymani; Aiman Farzeen; Holger Prokisch (Wiley, 2022)
ABSTRACT Although whole‐exome sequencing and whole‐genome sequencing has tremendously improved our understanding of the genetic etiology of human disorders, about half of the patients still do not receive a molecular diagnosis. The high fraction of variants with uncertain significance and the challenges of interpretation of noncoding variants have urged scientists to implement RNA sequencing (RNA‐seq) in the diagnostic approach as a high throughput assay to complement genomic data with functional evidence. RNA‐seq data can be used to identify aberrantly spliced genes, detect allele‐specific expression, and identify gene expression outliers. Amongst eight studies utilizing RNA‐seq, a mean diagnostic uplift of 15% has been reported. Here, we provide an overview of how RNA‐seq has been implemented to aid in identifying the causal variants of Mendelian disorders.